2004
DOI: 10.1080/13697130310001651490
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary supplementation with isoflavones from red clover on cognitive function in postmenopausal women

Abstract: Isoflavone supplementation does not appear to have major short-term effects on cognitive function in postmenopausal women. However, further clinical trials are required to determine whether small effects or long-term effects on cognitive function occur during isoflavone supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 16 publications
0
68
1
Order By: Relevance
“…Previous agents for the improvement of cognition all have side effects such as nausea, vomiting, etc. 19) Recently, it has been reported that the BF-7, a protein in the natural extract from Bombyx mori, exerted significant neuroprotection, functionally and physiologically. 20) For example, Lee et al showed that BF-7 protected SK-N-SH cells, human neuroblastoma cells, from reactive oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous agents for the improvement of cognition all have side effects such as nausea, vomiting, etc. 19) Recently, it has been reported that the BF-7, a protein in the natural extract from Bombyx mori, exerted significant neuroprotection, functionally and physiologically. 20) For example, Lee et al showed that BF-7 protected SK-N-SH cells, human neuroblastoma cells, from reactive oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, both Casini et al (84) and Santos et al (91) reported multiple t tests without any apparent correction for type I error. Howes et al (85) also carried out a large number of tests on a small sample (n 30) initially reporting a series of significant effects. However, as an illustration of good practice, these disappeared after the authors statistically accounted for type I error.…”
Section: Assessment Of Cognitive Performance In Existing Studiesmentioning
confidence: 99%
“…9 Adverse outcomes are occasionally described, 13 and observational findings raise concern of cognitive harm. 16,17 Given widespread interests in soy products among postmenopausal women 5,6 and controversial findings on cognitive function, [7][8][9][10][11][12][13][14][15] we sought to examine the long-term cognitive efficacy of soy isoflavones in the Women's Isoflavone Soy Health (WISH) trial. This study of healthy midlife and older women was designed to assess the effects of dietary supplementation with isoflavone-rich soy protein (ISP) containing naturally occurring isoflavones in quantities within the upper range of traditional Asian diets.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…Improved cognition is reported in some clinical trials [7][8][9][10] but not others. [11][12][13][14][15] Cognitive benefit is possibly restricted to younger postmenopausal women 6 or to specific cognitive domains. 9 Adverse outcomes are occasionally described, 13 and observational findings raise concern of cognitive harm.…”
Section: Classification Of Evidencementioning
confidence: 99%
See 1 more Smart Citation